Building Cultural Harmony and Self-Identity for Muslim Students in Darwin, Australia - Uswatun Hasanah; Ayu Reza Ningrum; Zaki Faddad Syarif Zain (Jurnal al-Thullab, 2025)
The growing presence of Muslim students in multicultural and secular societies, such as Australia, raises important questions about identity formation and cultural adaptation. This study aims to explore how Muslim students in Darwin construct cultural harmony and develop their self-identity within educational environments that may not fully accommodate religious practices. A descriptive qualitative approach was employed, using in-depth interviews, observations, and documentation involving students, parents, and community representatives, with thematic analysis applied to interpret the data. The findings reveal that Muslim students face multiple challenges, including limited access to worship facilities, lack of halal food, and experiences of stereotyping and social exclusion. Despite these constraints, they actively develop adaptive strategies such as effective time management, selective identity expression, and engagement in constructive dialogue, enabling them to balance academic and religious commitments. Islamic education plays a significant role in strengthening moral values, self-confidence, and a sense of belonging, while support from families, schools, and Muslim communities contributes to creating a more inclusive environment. This study contributes to the development of contextually responsive Islamic education and provides practical insights for enhancing student well-being, identity formation, and cultural harmony in multicultural settings.